2011
DOI: 10.1039/c1ra00261a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of cuprous oxide nanoparticles by laser ablation in PVP aqueous solution

Abstract: The cuprous oxide nanoparticles have been fabricated through pulsed laser ablation of copper target in PVP aqueous solution. The structure, morphology and composition of the nanoparticles have been characterized by X-ray powder diffraction (XRD), transmission electron microscopy (TEM), highresolution TEM (HRTEM), X-ray photoelectron spectroscopy (XPS) and X-ray excited auger spectra (XAES). The results show that the mean size of the as-prepared in diameter is about 29 nm with a relative narrow size distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
33
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 45 publications
10
33
0
1
Order By: Relevance
“…22,24,26,28 The mechanisms underlying the formation of copper Nps with pulsed laser ablation of a copper solid target in liquids are very complex. Oxidative processes of Cu Nps are complicated since copper has two oxidation states (Cu þ1 and Cu þ2 ) that form stable oxides with different activation energy barriers.…”
Section: Optical Extinction Calculationsmentioning
confidence: 99%
See 4 more Smart Citations
“…22,24,26,28 The mechanisms underlying the formation of copper Nps with pulsed laser ablation of a copper solid target in liquids are very complex. Oxidative processes of Cu Nps are complicated since copper has two oxidation states (Cu þ1 and Cu þ2 ) that form stable oxides with different activation energy barriers.…”
Section: Optical Extinction Calculationsmentioning
confidence: 99%
“…CuO type oxide of size less than 200 nm was formed in tightly focusing conditions, while Cu 2 O type oxide, of size under 10 nm, appeared for defocusing conditions. Recently, Liu et al 26 used the fundamental wavelength of a Nd:YAG laser to produce 30 nm diameter Cu 2 O Nps from laser ablation of an electrolytic copper plate immersed in PVP. XRD and electron diffraction patterns showed that Cu particles draughtdried at room temperature oxidized completely to Cu 2 O.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations